Detecção de Xanthomonas axonopodis pv. phaseoli em sementes, aspectos fisiológicos e proteção do feijoeiro contra o crestamento bacteriano comum usando extratos hidroalcoólicos de alecrim cúrcuma e Pycnoporus sanguineus - Dal'Maso, Emanuele Guandalin (2014)
The objective of this work, the control of common bacterial blight caused by Xanthomonas axonopodis pv. phaseoli (Xap) with the use of hydroalcoholic extracts of tumeric, rosemary and Pycnoporus sanguineus. In vitro was made the agar diffusion test with discs of filter paper and the detection of Xap in seed lots of beans of producers from the western region of Parana. Under field condition bean (IAPAR-81) was sprayed at 14, 28 and 42 days after the emergency, with the extracts at a concentration of 150 mL.L-1. Antibiotic (22,5 mg L-1 oxytetracycline + 225 mg L-1 of streptomycin) and water were the control treatments. The treatments were applied three days before inoculation of the pathogen. The evaluations were performed every three days for calculation of the area under the disease progress curve (AUDPC). Also it was evaluated number of seeds per pod and mass of grains, in two seasons January-June (2013). In the greenhouse, in pots of 8 L (two plants per pot), were daily assessments within a period of 7 days using infrared gas (IRGA), always in medial region of the third and fourth pair of new leaves and fully exposed to solar radiation, for verification of (A, μmol CO2 m-2 s-1), (gs, mmol H2O m-2 s-1), (E mmol H2O m-2 s-1), (EUA, mol m-2 s-1) and (EIUA, mol m-2 s-1). It was also performed the treatments with hydroalcoholic extracts of tumeric and rosemary in concentrations of 100, 150 and 200 mL L-1 in the third leaf stage, and on the fourth day of evaluations was performed the inoculation of bacteria. In the third and fourth leaves, in order to verify the induction of systemic resistance of extracts. For the agar diffusion test it was found no antimicrobial effect. Seed analysis indicated the presence of Xap in the samples. In vivo, treatment of tumeric presented lower AUDPC and greater productivity. In greenhouse it was observed that rosemary 150 mL L-1 o improved in 47%, in average the efficiency of water use (USA) local and systemically